Evaluasi Program Pembelajaran Kewirausahaan SMA Negeri 1 Prembun Kabupaten Kebumen - Eko Putro Widoyoko; Sri Kustilah; Sri Endah Pamilih (Jurnal Profit Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2020)
Abstract This study aims at determining the effectiveness of the entrepreneurship instructional program at SMAN 1 Prembun, Kebumen Regency in the academic year of 2018/2019. The evaluation model used is the EKO2P model. The population of the eleventh grade students majoring in social studies in the academic year of  2018/2019 consists of 156 students. The research sample of 101 students is determined based on the sample determination table by Isaac and Michael. Sampling is done by using a sample random sampling technique. Data collection instruments use the questionnaire method, document analysis, observation and interviews. Data analysis uses descriptive analysis.The results showed that instructional quality gained a score = 2.95 belonging to good qualifications, instructional output obtained a mean score = 3.03 belonging to good qualifications, instructional outcomes obtained a mean score = 2.62 belonging to good qualifications. The overall score of the quality, output, and outcome of entrepreneurship instructional program was 2.87 belonging to good qualifications. Thus, it can be concluded that the entrepreneurship programs at SMA Negeri 1 Prembun in the academic year of 2018/2019 has been implemented successfully.Keywords : instructional quality, instructional output, instructional outcome AbstrakPenelitian ini bertujuan untuk mengetahui efektivitas program pembelajaran kewirausahaan SMAN 1 Prembun Kabupaten Kebumen tahun ajaran 2018/2019. Model evaluasi yang digunakan adalah model EKO2P. Populasi semua siswa kelas XI jurusan IPS tahun pelajaran 2018/2019 berjumlah 156 siswa. Sampel penelitian sebanyak 101 siswa ditentukan berdasarkan tabel penentuan sampel dari Isaac dan Michael. Pengambilan sampel dengan teknik sample random sampling. Instrumen pengumpulan data menggunakan metode angket, analisis dokumen, observasi dan wawancara. Analisis data menggunakan analisis deskriptif.Hasil penelitian menunjukkan bahwa kualitas pembelajaran memperoleh skor = 2,95 dengan kualifikasi baik,  output pembelajaran memperoleh rerata skor = 3,03 dengan kualifikasi  baik, outcome pembelajaran memperoleh rerata skor = 2,62 kualifikasi baik. Rerata skor secara keseluruhan dari kualitas, output dan outcome program pembelajaran  kewirausahaan sebesar 2,87 kualifikasi baik.  Dengan demikian dapat disimpulkan bahwa program pembelajaran kewirausahaan di SMA Negeri 1 Prembun Kabupaten Kebumen tahun pelajaran 2018/2019 telah berjalan dengan baik.Kata-kata kunci : kualitas pembelajaran, output pembelajaran, outcome pembelajaran